The ‘Pedagogy of discomfort’: A qualitative exploration of non-indigenous student learning in a First Peoples health course - Mills, Kyly; Creedy, Debra (The Australian Journal of Indigenous Education, 2019)
Abstract To improve healthcare practices and increase cultural safety when working with First Peoples, it is essential that students engage with challenging discourses that critically engage their social, political, personal, professional and historical positioning. Such engagement may provoke emotional responses in students. However, little is known about the nature of non-indigenous students’ emotional engagement when learning First Peoples health content that integrates cultural safety principles. The pedagogy of discomfort is a process of self-examination that requires students to critically engage their ideological assumptions and may be useful in examining the emotional dimension that occurs when learning this content. Eighty-two non-indigenous health students gave permission for their critical reflective essays, submitted as an assessment requirement of a First Peoples health course to be analysed. Elements of the pedagogy of discomfort informed the analytical and theoretical framework. The emotional engagement by students was captured in the following overarching themes: Acknowledging preconceived ideas; Uncomfortable emotions; Fragile identities; Spectating and Witnessing. Findings highlight how students' emotional engagement may contribute to changes in perspective and frames of reference, transpiring to a ‘call to action’ that challenges systems of differential privilege. While many students expressed discomfort when learning about key cultural safety concepts, the extent of transformative potential varied.